THE EFFECT OF USING 3 MONTHLY INJECTION CONTRACEPTION (DEPOPROVERA) ON THE INCIDENCE OF MENOPAUSE - Sriwayanti; Deasy Irawati; Siti Anisak; Qurrotu Aini Cesari (Global Ten Public Health and Nursing Journal, 2024)
Menopause is the end of the last menstrual cycle but certainty is only obtained if a woman has not had her menstrual cycle for at least 12 months, in addition menopause occurs on average between the ages of 45-55 years. However, in terms of age, there are still mothers who experience late menopause who previously used the 3-month depoprovera injection contraceptive. This study aims to determine the effect of the use of the 3-month depoprovera injection contraceptive on the incidence of menopause in the Demangan Village study group. The design of this study is analytical. The population used were mothers aged 45-55 years who had previously used 3-month depoprovera injection contraception for > 2 years. The independent variable is the use of 3-month depoprovera injection contraception, the dependent variable is menopause . The population was 15 mothers. Data collection used a questionnaire. Tested using the fisher's exact test with a significance level of 0.05. The results of the study on 15 mothers in table 4.6, those who experienced late menopause were 9 mothers (60%), normal menopause was 6 mothers (40%). Based on the fisher's exact test , the probability value (0.01) was smaller than the significance level value (0.05) so it was rejected and accepted. In conclusion, there is an effect of the use of 3-month depoprovera injection contraception on the incidence of menopause . To improve the health status of women, midwives are expected to emphasize more on the side effects of 3-month depoprovera injection contraception in providing HE.